Demonising demonstration: (de) legitimization strategies through emotions in the speeches of Hosni Mubarak and Ben Ali - Sulaiman, Abdul Kadir; Mohamad Jamil, Siti Nurnadilla (IDOSI Publications, 2014)
From an interdisciplinary framework anchored theoretically in Critical Discourse Analysis (CDA) and using Systemic Functional Linguistics (SFL), this article proposes to explain the (de) legitimization strategies employed by Arab leaders and to study the linguistic choices associated with those schemes. The strategy of legitimization through emotions (one of the five strategies of legitimization proposed by [1]) is applied in the analysis of the spoken languages of two chosen Arab leaders; former president of Tunisia, Ben Ali (FPBA) and one-time president of Egypt, Hosni Mubarak (FPHM) in which both addressed the subject of demonstrations during the Arab Spring. Both FPBA and FPHM delivered, respectively, three speeches while facing the Arab Spring demonstrations. The analyses pay special attention to whether the use of the (de) legitimization strategy through emotions and the usage of language are consistent or whether they evolve from the first to the second and to the third speech. The key findings of this study reveal that both presidents (FPBA and FPHM) potrayed themselves positively and the demonstrators negatively, through the choice of (de)legitimization strategies. In addition, this research also discovered that the linguistic choices made by the leaders clearly indicate that relational values are evident in choosing vocabulary and grammar especially in those of FPHM. Above all, it became apparent that the strategies and the linguistic choices of both presidents evolved throughout their three speeches, but the evolutions of those of FPBA are more obvious than those of FBHM.